2019
DOI: 10.1021/jacs.8b13358
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Electrostatic Interaction Model Revised: Prediction Comes Mainly from Measuring Charge Accumulation in Hydrogen-Bonded Monomers

Abstract: The secondary electrostatic interaction (SEI) model is often used to predict and explain relative hydrogen bond strengths of self-assembled systems. The SEI model oversimplifies the hydrogen-bonding mechanisms by viewing them as interacting point charges, but nevertheless experimental binding strengths are often in line with the model’s predictions. To understand how this rudimentary model can be predictive, we computationally studied two tautomeric quadruple hydrogen-bonded systems, DDAA-AADD and DADA-ADAD. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 60 publications
(78 reference statements)
3
62
0
Order By: Relevance
“…However,t here are also cases in which this dipole-dipole interpretation fails to explain the geometricala nd energetic trends, such as the nonlinearity of the HF dimer [14] or the large energetic differences between dimers with similard ipole moments. [10] More recently,T iwari and Vanka [25] proposed to use the electrostatic force (whichh as directionality) rathert han the electrostatic interaction for the description of noncovalent interactions. Good correlations were found between the electrostatic forces and the binding energy for aw ide range of systems, including 28 base pairs that were studied in ref.…”
Section: Electrostatic Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…However,t here are also cases in which this dipole-dipole interpretation fails to explain the geometricala nd energetic trends, such as the nonlinearity of the HF dimer [14] or the large energetic differences between dimers with similard ipole moments. [10] More recently,T iwari and Vanka [25] proposed to use the electrostatic force (whichh as directionality) rathert han the electrostatic interaction for the description of noncovalent interactions. Good correlations were found between the electrostatic forces and the binding energy for aw ide range of systems, including 28 base pairs that were studied in ref.…”
Section: Electrostatic Interactionmentioning
confidence: 99%
“…[75][76][77][78][79] When these factorsa re comparable, the dispersion interactions are usually of similar strength. [10,76] However,w hen one or more of these factors are significantly different, dispersion might even determine the trend in interaction strength.T hisw as shown by Hoja et al by studying( XOH) 2 with X = H, Me, Et, nPr, nBu, iPr and tBu. [76] They found that the interaction energy between two H-bonded monomers becomes 58 %s tronger when going from the smallest dimer (H 2 O) 2 to the bulkiest dimer (tBuOH) 2 (Figure 7).…”
Section: Dispersion Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Figures 3 and 5). The two water molecules coordinated by the Ni II atom and hydrogen bonded to the carboxylate show an attractive secondary electrostatic interaction [44,45] in the formed hydrogen-bonding pattern. The arrangement is similar to that found in the hydrogen bonded complex between the guanine and cytosine of nucleic acids [44,46].…”
Section: Description Of the Crystal Structurementioning
confidence: 99%